Domestic carnivore interactions with wildlife in the Cape Horn Biosphere Reserve, Chile: husbandry and perceptions of impact from a community perspective - Schuttler, Elke; Saavedra-Aracena, Lorena; Jimenez, Jaime E. (My University, 2018)
Background. Hundreds of millions of domestic carnivores worldwide have diverse positive affiliations with humans, but can provoke serious socio-ecological impacts when free-roaming. Unconfined dogs (Canis familiaris) and cats (Felis catus) interact with wildlife as predators, competitors, and disease-transmitters; their access to wildlife depends on husbandry, perceptions, attitudes, and behaviors of pet owners and non-owners. Methods. To better understand husbandry and perceptions of impacts by unconfined, domestic carnivores, we administered questionnaires (n = 244) to pet owners and non-owners living in one of the last wilderness areas of the world, the Cape Horn Biosphere Reserve, located in southern Chile. We used descriptive statistics to provide demographic pet and husbandry information, quantify free-roaming dogs and cats, map their sightings in nature, and report experiences and perceptions of the impact of free-roaming dogs and cats on wildlife. We corroborated our results with an analysis of prey remains in dog feces (n = 53). With generalized linear models, we examined which factors (i.e., food provisioning, reproductive state, rural/village households, sex, and size) predicted that owned dogs and cats bring wildlife prey home. Results. Thirty-one percent of village dogs (n = 121) and 60% of dogs in rural areas (n = 47) roamed freely day and/or night. Free-roaming dog packs were frequently observed (64% of participants) in the wild, including a feral dog population on Navarino Island. Dogs (31 of 168) brought home invasive muskrats (Ondatra zibethicus) and avian prey, and over half of all cats (27 of 51) brought home mainly avian prey. Birds were also the most harassed wildlife category, affected by one third of all dogs and cats. Nevertheless, dog-wildlife conflicts were hardly recognized (< 9% of observed conflicts and suspected problems), and only 34% of the participants thought that cats might impact birds. Diet analysis revealed that dogs consumed livestock (64% of 59 prey occurrences), beavers (Castor canadensis, 14%), and birds (10%). The probability that dogs brought prey to owners' homes was higher in rural locations and with larger dogs. There was also evidence that cats from rural households and with an inadequate food supply brought more prey home than village cats. Discussion. Although muskrat, beavers, and birds were brought home, harassed, or found in dog feces, free-roaming dogs and, to a lesser extent, cats are perceived predominantly in an anthropogenic context (i.e., as pets) and not as carnivores interacting with wildlife. Therefore, technical and legal measures should be applied to encourage neutering, increase confinement, particularly in rural areas, and stimulate social change via environmental education that draws attention to the possibility and consequences of unconfined pet interaction with wildlife in the southernmost protected forest ecoregion of the globe.
Keywords: conservation; domestic cat (felis catus); domestic dog (canis familiaris); free-roaming; invasive species; predation; protected area; questionnaires; sub-antarctic; survey